2021
DOI: 10.1001/jama.2020.24071
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Outcomes of SARS-CoV-2 Infection Among Migrant Workers in Singapore

Abstract: High-density communal residences are at elevated risk of large outbreaks of respiratory disease. 1,2 After an initial nationwide outbreak of 231 cases of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections in Singapore, which was contained as of March 24, 2020, a surge of 244 cases among migrant workers residing in dormitories, largely from Bangladesh and India, occurred from March 25 to April 7. A national task force was formed to coordinate Singapore's outbreak response. A national lockd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 3 publications
3
39
0
3
Order By: Relevance
“…Longitudinal serology in asymptomatic SARS-CoV-2 infection Beginning in April 2020, Singapore experienced large outbreaks of SARS-CoV-2 infections among migrant workers residing in densely populated dormitories (Fig. 1 A; Tan et al, 2021b). To select asymptomatic individuals who were exposed to SARS-CoV-2 at different time points, we followed up on 478 residents of a SARS-CoV-2-affected dormitory who donated blood at recruitment and 2 and 6 wk later for serological testing of anti-NP IgG and neutralizing antibodies (nAbs; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Longitudinal serology in asymptomatic SARS-CoV-2 infection Beginning in April 2020, Singapore experienced large outbreaks of SARS-CoV-2 infections among migrant workers residing in densely populated dormitories (Fig. 1 A; Tan et al, 2021b). To select asymptomatic individuals who were exposed to SARS-CoV-2 at different time points, we followed up on 478 residents of a SARS-CoV-2-affected dormitory who donated blood at recruitment and 2 and 6 wk later for serological testing of anti-NP IgG and neutralizing antibodies (nAbs; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The asymptomatic cohort comprised 541 men aged 19-59 yr (median 35 yr) recruited from randomly selected rooms within a SARS-CoV-2-affected dormitory housing >4,000 migrant workers largely from India and Bangladesh (∼86% ; Table S2) and followed up prospectively from May to July 2020 (Tan et al, 2021b). Detailed information about the measures to contain SARS-CoV-2 outbreaks in the dormitories can be found at the Singapore Ministry of Manpower website (https://www.mom.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from our study indicated that around two-thirds of dormitory residents had been infected between April and early July, in line with seroprevalence estimates reported from other migrant worker populations. 1 Moreover, our data suggest extremely high infection risks in these settings, with more than half of initially immunologically naive individuals becoming infected over the six-week follow-up period. Crowded, poorly ventilated indoor spaces are known to be high-risk environments for SARS-CoV-2 transmission, and have been associated with large outbreaks among processing plant workers.…”
Section: Discussionmentioning
confidence: 71%
“…However, from March 2020, Singapore experienced a series of large epidemics in densely populated migrant worker dormitories. 1 In response, workers were con ned to dormitories during the lockdown period and movement within dormitories was restricted. Medical teams were deployed in all dormitories to provide testing and refer suspected COVID-19 cases to healthcare facilities, leading to the eventual interruption of transmission in September 2020.…”
Section: Introductionmentioning
confidence: 99%